Teachers’ Challenges in Developing Children’s Character in Multicultural and Inclusive Classroom - Komang Dendi Krisna Murti; Ni Nyoman Padmadewi; Luh Gd Rahayu Budiarta (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
This study aims to examine the challenges faced by teachers in implementing the Montessori method to develop children's character in multicultural and inclusive classrooms. A qualitative approach with a case study design was conducted at Singaraja Montessori School in the Octopus class. Among the participants in this study were two teachers who teach in the Octopus class. Research data were collected through three methods: classroom observation, semi-structured interviews, and document analysis. Then, they were analyzed using the Miles and Huberman analysis model, which includes data reduction, data presentation, and drawing conclusions. The research findings indicate three challenges. First, teachers face challenges in understanding the characteristics and needs of new students. Second, there are challenges in managing diverse classes. Third, teachers have limited experience in inclusive education. This study confirms that developing children's character in diverse classes requires continuous observation, flexible classroom management, and teacher readiness to respond to the diverse needs of students.